A COMBINED METHOD OF 1D AND 2D RESISTIVITY FOR GROUNDWATER LAYER ESTIMATION AT A FARMING AREA IN REJOMULYO VILLAGE - Antosia, Risky Martin; Ramdan, Muhammad (Program Studi Fisika Universitas Negeri Jakarta, 2023)
The groundwater depends on when it is available, more in the rainy and less in the dry seasons. Fluctuation in water availability is a significant problem in activities continuously requiring large amounts of water, such as agriculture. Hence, it is necessary to increase the number of water resources to meet the community's needs. Therefore, the groundwater layer zone was estimated as an initial study at the dry farmland in Rejomulyo village, Jati Agung district, South Lampung, using a combined method between the 1D resistivity method of the Schlumberger array and the 2D form of the Wenner configuration. Each sounding point and the 2D line have a maximum stretch length of 300 m. The 1D outcome correlates to the 2D data processing result to produce a subsurface lithology model. As a result, the research area has three primary layers with three rock types. The first layer has a resistivity value of less than 20 Ωm and is identified as tuffaceous clay. Then the second layer with a resistivity range of 60–66 Ωm is tuffaceous sand, this rock which is referred to as the groundwater layer with a depth of 11-40 m. The last layer has a high resistivity value of 120–141 Ωm as tuff. Based on the results of 3D visualization, the groundwater layer in the study area spreads to the southeast with a confined aquifer type. This targeted rock layer can be utilized for groundwater production.